Afatinib for Advanced Non-small Cell Lung Cancer in a Case With an Uncommon Epidermal Growth Factor Receptor Mutation (G719A) Identified in the Cerebrospinal Fluid - Ma, Chunhua; Huang, Chuoji; Tang, Dongjiang; Ye, Xin; Li, Zhi; Liu, Renzhong; Mu, Ning; Li, Jing; Jiang, Rong; Zhang, Juncheng (Frontiers in Oncology, 2019)
Few previous studies of patients with non-small cell lung cancer (NSCLC) and leptomeningeal metastases have used liquid biopsy of cerebrospinal fluid (CSF) to identify epidermal growth factor receptor (EGFR) mutations and guide therapy. A 34-year-old male patient with NSCLC and leptomeningeal metastases was admitted to the Interventional Radiology Department, Tianjin Huanhu Hospital on 18th April 2018 after showing no response to chemoradiotherapy. On admission, the patient was in critical condition with an estimated survival <1 month. A ventriculoperitoneal shunt was placed in the right lateral ventricle. The CSF level of carcinoembryonic antigen (CEA) was 9,869 ng/mL. Next-generation sequencing (NGS) of the CSF revealed an EGFR G719A mutation (frequency: 55.63%), whereas sequencing of circulating tumor DNA or cells in the peripheral blood identified no clinically significant mutations. Afatinib therapy was initiated based on the NGS results. During follow-up, the patient's symptoms improved, ventricular dilatation lessened, and pulmonary lesions decreased in size. At the last follow-up (7 months), the patient continued to show a good response to afatinib therapy with minimal adverse effects. This is the first clinical study to report the use of simultaneous genetic testing of CSF and peripheral blood to guide the successful implementation of afatinib therapy in a patient with NSCLC and leptomeningeal metastases. Notably, NGS of CSF was superior to genetic testing of peripheral blood at identifying an uncommon EGFR mutation (G719A) in a patient with NSCLC and leptomeningeal metastases.